Work-Life Balance in the Hybrid Working Model: A Systematic Literature Review - Intan Tamara Febrinzky (Journal of Applied Digital Business Management, 2025)
One of the impacts that arose after the pandemic is hybrid working. Hybrid working describes an individual's ability to work remotely or not be present in the office environment. This has also become one of the drivers for the work-life balance campaign. The methods used are literature review and books. With a source limit of a maximum of 5 years back, but exceptions will be made if the data is considered important. The results of this review are significant and can provide input and mitigation for companies so that hybrid working brings more benefits than drawbacks by imposing additional burdens on employees.